Novel fiber-based pure chitosan scaffold for tendon augmentation: biomechanical and cell biological evaluation. Issue 10 (2nd July 2016) - Nowotny, J.; Aibibu, D.; Farack, J.; Nimtschke, U.; Hild, M.; Gelinsky, M.; Kasten, P.; Cherif, Ch.
Abstract: One possibility to improve the mechanical properties after tendon ruptures is augmentation with a scaffold. Based on wet spinning technology, chitosan fibres were processed to a novel pure high-grade multifilament yarn with reproducible quality. The fibres were braided to obtain a 3D tendon scaffold. The CS fibres and scaffolds were evaluated biomechanically and compared to human supraspinatus (SSP) tendons. For the cytobiological characterization, in vitro cell culture experiments with human mesenchymal stem cells (hMSC) were performed. Three types of 3D circular braided scaffolds were fabricated. Significantly, higher ultimate stress values were measured for scaffold with larger filament yarn, compared to scaffold with smaller filament yarn. During cultivation over 28 days, the cells showed in dependence of isolation method and/or donor a doubling or tripling of the cell number or even a six-fold increase on the CS scaffold, which was comparable to the control (polystyrene) or in the case of cells obtained from human biceps tendon even higher proliferation rates. After 14 days, the scaffold surface was covered homogeneously with a cell layer. In summary, the present work demonstrates that braided chitosan scaffolds constitute a straightforward approach for designing tendon analogues, maintaining important flexibility in scaffold design and providing favourable mechanical properties of the resulting construct.